Collaborative Management Between Parents and Teachers to Create an Inclusive School - Amanda Handya Putri; Alpino Susanto; Linayati Lestari (Jurnal Inovasi Pendidikan dan Sains, 2025)
Inclusive education provides learning opportunities for all children, including those with special needs, within the same environment. This study aims to analyze the collaborative management between parents and teachers in creating an inclusive school at Cahaya Meral Private Junior High School, as well as to identify the challenges and strategies to address them. A mixed methods approach was used by combining quantitative data from questionnaires distributed to 5 parents and 4 teachers, and qualitative data from observations and in-depth interviews.The results show that the implementation of inclusive education at Cahaya Meral Private Junior High School still faces several obstacles, such as limited facilities and infrastructure, lack of training for educators, and delays in identifying the needs of students with special needs. Nevertheless, the synergy between teachers and parents has contributed positively to the development of these children. The principal plays a crucial role in providing training and resources necessary to foster an inclusive learning environment.To enhance the effectiveness of inclusive education, continuous teacher training and the provision of adequate facilities, such as therapy rooms and learning aids, are required. Strong communication and cooperation among all stakeholders are also essential. These findings are expected to serve as a reference in formulating more optimal inclusive education policies, so that every child can access equitable and quality education